Evaluation of Sex and Age Influence on Plagiarism as Academic Dishonest Behaviour among Postgraduate Students of Federal Universities in South-South Zone of Nigeria - Julius Michael Egbai (Har Press Indonesia, 2021)
The study investigated evaluation of sex and age influence on plagiarism as academic dishonest behaviour among postgraduate students of federal universities in South-South, Nigeria. The study which is a survey research, involved a multi-stage stratified random sampling technique of 440 males and 490 females from 3 universities and 3 faculties of the same universities in South-South, Nigeria. The sample was selected through a stratified random sampling approach. The study adopted frequencies, percentages, factor analysis and multiple classification analysis statistical tools. A questionnaire developed and validated by the researcher titled: